Rancangan Pelayanan Bimbingan Konseling pada Abad 21 - Muhammad Fajri Tsani Ramadhani (Universitas Pancasakti Tegal, 2022)
Guidance and Counseling (BK) as a process of providing assistance to individuals (students) can be carried out through various services. Currently these services are growing, not only can be done face-to-face directly, but also by utilizing existing media or information technology. The goal is to make the counseling process more interesting, interactive, and innovative, not hampered by space and time, but still paying attention to the principles and code of ethics in guidance and counseling. Furthermore, here are some innovations in providing Counseling Guidance services to SMK students